2001
DOI: 10.1002/hfm.1013
|View full text |Cite
|
Sign up to set email alerts
|

Coping with job stress in industries: A cognitive approach

Abstract: This study examined the roles of the coping strategies used by individuals to cope with job stress. The coping strategy was formed throughout the cognitive appraisal of the stressful events. It was found that direct action coping strategy shows negative relations with job stressors, whereas there are positive relations between stressors and other coping strategies. This implies that direct action coping strategy is used to alleviate the job stress by affirmatively changing the deleterious effects of job stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…Moreover, many studies have suggested that social support may be a very useful resource in preventing the development of burnout (Bakker, Demerouti, & Verbeke, 2004;Glasberg, Eriksson, & Norberg, 2007;Lindblom, Linton, Fedeli, & Bryngelsson, 2006). On the other hand, avoidant strategies have been generally found to increase emotional exhaustion, and decrease work achievement (Evans, Bryant, Owens, & Koukos, 2004;Haar, 2006;Lee & Lee 2001;Okabayashi et al, 2008;van Rhenen et al, 2008;Wallace et al, 2010). This result is consistent with the one of earlier studies, indicating a negative relationship between denial and health (eg.…”
Section: Stress and Copingsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, many studies have suggested that social support may be a very useful resource in preventing the development of burnout (Bakker, Demerouti, & Verbeke, 2004;Glasberg, Eriksson, & Norberg, 2007;Lindblom, Linton, Fedeli, & Bryngelsson, 2006). On the other hand, avoidant strategies have been generally found to increase emotional exhaustion, and decrease work achievement (Evans, Bryant, Owens, & Koukos, 2004;Haar, 2006;Lee & Lee 2001;Okabayashi et al, 2008;van Rhenen et al, 2008;Wallace et al, 2010). This result is consistent with the one of earlier studies, indicating a negative relationship between denial and health (eg.…”
Section: Stress and Copingsupporting
confidence: 86%
“…problem-solving, and seeking social support) could not have been confirmed in a consistent manner (see Folkman & Moskowitz, 2004). More recent studies, however, have found that active problemsolving results in a lower level of stress at work such as decreased distress, burnout, and better general mental health (Lee & Lee, 2001;Ro et al, 2010;Shimazu & Kosugi, 2003;van Rhenen, Schaufeli, van Dijk, & Blonk, 2008). Active coping strategies (problem-solving, and seeking social support) moderate negatively the relationship between work stress and burnout (Lee & Lee 2001;Wallace, Lee & Lee, 2010).…”
Section: Stress and Copingmentioning
confidence: 97%
See 1 more Smart Citation
“…Existe uma incerteza de que o esforço levado a cabo seja suficiente para atingir o desempenho esperado, não pelo facto do trabalhador duvidar das suas competên-cias, mas pelo tempo que tem disponível. Portanto, quando isto acontece, os indivíduos experienciam tensões físicas e psicológicas que têm uma relação com o stress no trabalho (Kendall et al, 2000;Lee & Lee, 2001;Santos et al, 2008).…”
Section: Clima Organizacional E Condições De Trabalhounclassified
“…Além disso, possuem níveis mais elevados de satisfação no trabalho, menos queixas somáticas, uma menor incidência de depressão e ansiedade. Parece, portanto, que estas pessoas procuram formas de terem um maior controlo das situações e tendem a olhar para elas com mais otimismo (Lee & Lee, 2001). Todavia, importa realçar que estes fatores de vulnerabilidade pessoais não são estáticos e podem variar num mesmo indivíduo ao longo do tempo e consoante o contexto (Ladeira, 1996).…”
Section: Resiliência Psicológica E Estilos De Copingunclassified